1973
DOI: 10.21236/ad0760140
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Absorption Coefficients for Eleven CO Laser Lines

Abstract: Sponsored by Dafense Advanced Research Project! Agency ARPA Order No. 1279 ycrcrc Approved for public release: distribution unlimited. The views and conclusions contained in this document are those of It ;S«T,-nd^Uld ^ b ' lnt^r eted as neceaearily repenting the officisl policies, either expressed or Implied, of the Defense Advanced Rasssrch Project. Agency or the V.S. GovirSeJt?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At frequencies removed from line center, the Lorentz line shape does not in general give an accurate representation of the true line shape. Long, et al [12] found that water vapor window absorption between 5 and 6 microns could be more accurately predicted by a line shape having more absorption in the wings than the Lorentz profile. Also Benedict, et al [13] found that for the fundamental band of CO the absorption in the wings of lines was less than predicted by the Lorentz shape.…”
Section: Ricchj Gives a Good Discussion Of The Complexity Of The Detementioning
confidence: 99%
See 2 more Smart Citations
“…At frequencies removed from line center, the Lorentz line shape does not in general give an accurate representation of the true line shape. Long, et al [12] found that water vapor window absorption between 5 and 6 microns could be more accurately predicted by a line shape having more absorption in the wings than the Lorentz profile. Also Benedict, et al [13] found that for the fundamental band of CO the absorption in the wings of lines was less than predicted by the Lorentz shape.…”
Section: Ricchj Gives a Good Discussion Of The Complexity Of The Detementioning
confidence: 99%
“…The other main divference is that the Lorentz line shape is not used, but rather a modification of the Lorentz line shape suggested by T;-usty [12]. The alternate shaoe has the form…”
Section: Fig 6 Example Run Of Spectra Plotting Programmentioning
confidence: 99%
See 1 more Smart Citation